CD19 and CD70 Dual-Target Chimeric Antigen Receptor T-Cell Therapy for the Treatment of Relapsed and Refractory Primary Central Nervous System Diffuse Large B-Cell Lymphoma - Tu, Sanfang; Zhou, Xuan; Guo, Zhenling; Huang, Rui; Yue, Chunyan; He, Yanjie; Li, Meifang; Chen, Yiran; Liu, YuChen; Chang, Lung-ji; Li, Yuhua (Frontiers in Oncology, 2019)
Background: The therapeutic efficacy of chimeric antigen receptor (CAR) T-cells targeting CD19 has been illustrated in the treatment of diffuse large B-cell lymphoma (DLBCL). However, there is a 21–35% relapse rate after anti-CD19 CAR T-cell induced remission. In addition, CAR T-cell therapy has severe adverse reactions, such as cytokine release syndrome (CRS) and CART-related encephalopathy syndrome (CRES). Because of the potential mortality associated with severe CRES, patients with primary central nervous system lymphoma (PCNSL) are usually excluded from clinical trials involving CAR T-cell therapy. Here, we report a case of refractory and relapsed primary central nervous system diffuse large B-cell lymphoma (PCNS-DLBCL). Case presentation: The patient is a 67-year-old male who was diagnosed with PCNSL in 2011. He achieved complete remission (CR) after receiving 6 cycles of temozolomide and high-dose methotrexate. In December 2016, he experienced his first relapse and was treated with surgery and multicourse chemotherapy. He achieved CR again after the treatment. However, he experienced a second relapse in August 2017. MRI revealed a residual mass of 26 mm*35 mm*30 mm on the right side of the postoperative cavity and stale hemorrhage in the left basal ganglia. After confirming the expression of CD19 and CD70 in his tumor samples, the patient was given lymphodepletion chemotherapy followed by infusion of 4th generation CD19-CAR T-cells (4SCART19) and 4th generation CD70-CAR T-cells (4SCART70). One month later, the patient had symptomatic improvement, and brain MRI showed CR. Both CART19 and CART70 cells were detected in the 10th month after CAR T-cell infusion. Notably, neither CRS nor CRES occurred during treatment and follow-up. To date, the patient has maintained disease-free survival with more than 17 months of follow-up. Conclusions: The results of this study indicate that combination of CD19- and CD70-specific CAR T-cells may effectively target PCNSL and maintain disease-free survival without inducing CRS or CRES. Therefore, central nervous system lymphoma is not an absolute contraindication for dual-target CAR T-cell therapy.